2022
DOI: 10.3389/fenvs.2022.982160
|View full text |Cite
|
Sign up to set email alerts
|

Can performance-based budgeting reform improve corporate environment in ESG? Evidence from Chinese-listed firms

Abstract: Finance is a pillar industry of national governance. It also provides a solid guarantee for achieving the official Double Carbon target. The question of how to forefront the role of environmental governance in the reform of fiscal and taxation systems, whilst also motivating enterprises to enhance Environment in Environmental, Social, and Governance (EESG) considerations is worth investigating in depth. This study takes A-share listed companies in China from 2001 to 2020 as examples. The effect of Performance-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…For example, Piatti‐Fünfkirchen and Schneider (2018) studied the health service delivery in Tanzania and Zambia and found that rigid control and inadequate attention to equity, quality, and efficiency in the performance‐based financial management system have hurt service outcomes. Wang and Hu (2022) studied how the Chinese performance‐based budgeting reform impacts the environmental, social, and governance reporting of enterprises and China's carbon neutrality efforts.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Piatti‐Fünfkirchen and Schneider (2018) studied the health service delivery in Tanzania and Zambia and found that rigid control and inadequate attention to equity, quality, and efficiency in the performance‐based financial management system have hurt service outcomes. Wang and Hu (2022) studied how the Chinese performance‐based budgeting reform impacts the environmental, social, and governance reporting of enterprises and China's carbon neutrality efforts.…”
Section: Resultsmentioning
confidence: 99%
“…As per the research conducted by Wang and Hu, Mu et al and Lu et al [ [ [44] , [45] , [46] ]], this paper defines a range of control variables , from three perspectives: corporate financial indicators, governance structure and regional factors. Meanwhile, this paper deflates the variables Size and Gdp based on China's inflation rates in each year, using 2011 as the base period.…”
Section: Methodsmentioning
confidence: 99%
“…They are all free version without licenses. [1], [2], [3], [4], [5], [6], [7], [8] , [9], [10], [11], [12], [13] , [14], [15], [16], [17], [18], [19], [20], […”
Section: Appendixmentioning
confidence: 99%